Drivers of leafcutter ant populations and their inter‐trophic relationships in Amazonian forest islands. Issue 5 (24th May 2021) - Palmeirim, Ana Filipa; Benchimol, Maíra; Leal, Inara R.; Peres, Carlos A.
Abstract: Under habitat loss and fragmentation, the intensity of local ecological processes involving species interactions changes pervasively, accelerating local species extinctions, and disrupting essential ecosystem functions. We addressed this issue by examining the direct population drivers of apex predators (five felid species), armadillo mesopredators, leafcutter ants ( Atta sexdens and Atta cephalotes ), and the indirect effects mediated by their inter‐trophic relationships in a 25‐yr‐old land‐bridge island system formed by a hydroelectric dam in the Central Amazon. These trophic groups and pioneer tree abundance were surveyed across 34 variable‐sized islands and three continuous forest sites. Leafcutter populations were characterized in relation to their occurrence, colony density, and proportion of inactive colonies, and for each leafcutter response, we considered the direct and/or indirect effects of forest area on each trophic group. Leafcutter occupancy was best explained by the direct model, colony density by either the direct or the indirect model, and proportion of inactive colonies by an indirect model via the effects of pioneer tree abundance. The direct forest area effects were positive for apex predators and leafcutter occupancy, but negative for armadillos and pioneer trees. Yet leafcutter colony density declined in increasingly larger forest areas. The absence or low abundance of apex predators on small islands released armadillo hyper‐abundance, which contrary to expectation from top‐down control, covaried positively with leafcutter colony density. Finally, the indirect model showed that leafcutter colonies were more active under higher pioneer tree abundances. That leafcutter density increases on smaller islands whenever present is likely attributed to the hyper‐abundance of pioneer plants and canopy gaps. Although apex predators apparently suppressed armadillos, the remaining fraction of the food web seems to be controlled by bottom‐up mechanisms most likely related the overall low foliage palatability typical of wet evergreen forests. Our findings can be used to inform the long‐term viability of forest ecosystems affected by hydropower development in lowland Amazonia.